Pengaruh Jumlah Donor Hipofisis Ikan Mas (Cyprinus carpio Lin) terhadap Keragaan Reproduksi Ikan Lele Sangkuriang (Clarias sp) - Hamdan Jamal (Universitas Padjadjaran, 2011)
The objective of research is to identify the number of carp pituitary donors providing an effect on the quickest latency time of ovulation, the highest percentages of the egg hatching rate and survival rate larvae. In this research there were 6 treatments and 3 replications where A was 1 tail donor with the weight 600 gram, B was 2 tails donor with the individually weight 600 gram, C is 3 tails donor with the individually weight 200 gram, D is 1 tail donor with the individually weight 1200 gram, E is 2 tails donor with the individually weight 600 gram and F is 3 tails donor with the individually weight 400 gram, whereas the mother or tested fish’s weight is 600 gram. The result of research indicates that the number of fish donors in the pituitary gland injecting has had effects on the latency time of ovulation where in the treatment of F provided the quickest time of 8,30 hours, the next the treatment of E with the time of 9,40 hours, the treatment of D with the time of 9,64 hours, the treatment of B with the time of 9,70 hours, the treatment of A with the time of 9,76 hours, and the treatment of C with the time of 10,48 hours. At the observation to the egg hatching rate tested the number of eggs hatched is 500 eggs, the result of research shows that the highest percentage at the treatment of F with 94.66%, the next the treatment of E with 92.93%, the treatment of D with 92.26%, the treatment of A with 90.86%, the treatment of B with 90.53%, and the smallest at the treatment of C with 89.33%. The research to the number of fish donors has no real effects on the survival rate larvae.